Legal Protection for Children Working Under Age: Normative and Implementative Studies - Dodi Harisandy; Jenriswandi Damanik; Desy Kartika C. Sitepu (Academic Solution Publisher, 2024)
Cases of underage employment and discrimination against child workers—such as being forced into street performing, begging, construction labor, or commercial sexual exploitation—remain prevalent in society, despite clear legal prohibitions under Indonesia’s Child Protection Law. This study explores three key issues: (1) the legal protection mechanisms for underage workers, (2) government efforts to address child labor, and (3) the challenges faced in enforcing child labor laws through a dual-method research approach, combining library research (literature review) and field research (empirical study). The findings indicate that legal protection for child labor victims in Pematang Siantar involves strict legal actions against perpetrators, alongside active community participation—including individuals, child protection agencies, social organizations, NGOs, educational institutions, religious bodies, businesses, and mass media—all of which must operate in accordance with existing laws (Law No. 35/2014). Additionally, the government promotes community involvement through social institutions and NGOs, encouraging them to actively contribute to child protection programs and assist underage workers in accessing support services. However, significant challenges persist, including unequal access to free education for underprivileged children and law enforcement’s focus on curative rather than preventive measures, which fails to address the root causes of child labor and allows exploitation to persist